Enzymatic synthesis of palm oil-based trimethylolpropane ester as biolubricant base stock catalyzed by Lipozyme 435 - Abd Wafti, Nur Sulihatimarsyila; Yunus, Robiah; Lau, Harrison Lik Nang; Shean, Thomas Yaw Choong; Abd Aziz, Suraini (Elsevier, 2022)
The application of enzymes in the organic synthesis of polyol esters for biolubricants is one of the initiatives in the development of sustainable processes in the oil palm industry. In this study, trimethylolpropane (TMP) ester was synthesized from high oleic palm methyl ester (HO-PME) via enzymatic transesterification. Lipozyme 435, which is an immobilized form of lipase B from Candida antarctica (CALB), was investigated as a substitute for chemical catalyst in the production of palm oil-based lubricant. Response surface methodology (RSM) via Central Composite Rotatable Design was employed to optimize the reaction conditions. The results showed that only 3% (w/w) enzyme dosage was required to obtain the highest triester of 82% without purification. The optimum process conditions predicted by RSM were 3.45:1 M ratio of HO-PME: TMP, 15.25 mbar pressure, and 48 h reaction time. The TMP ester exhibited excellent lubricant properties. This study demonstrated a reduction in overall production cost including waste management due to the elimination of the product purification step. As compared to chemical catalyst, milder reaction conditions and no formation of side products were observed in this study. The physicochemical characteristics of the TMP ester synthesized via enzymatic transesterification complied satisfactorily with the requirements of biolubricant base stock. Our findings offer a greener and economical approach for producing high-performance biolubricant, which can be applied for scale-up production.